The Effect of Organizational Culture and Transformational Leadership on Employee Performance through Job Satisfaction - Parulian Halomoan Butarbutar; Nancy Yusnita; Herdiyana Herdiyana (Budapest International Research and Critics University, 2022)
Research related to employee performance show that many factors affect to the employee performance either directlly or indirectlly. The purpose of this study is to empirically examination the factors that influence employee performance, indirect factors are organizational culture and transformational leadership and indirect factor is job satisfaction. This research was conducted at Yayasan Gugah Nurani Indonesia/GNI affiliate of Good Neighbors International and used quantitative data (from questionnaires). The research sample consisted of 140 employees of the Yayasan Gugah Nurani Indonesia/GNI. SEM analysis was used to determine the effect of the research variables. The results showed, that there was a positive and significant influence of organizational culture on employee performance; a positive and unsignificant effect of transformational leadership on employee performance; a positive and significant effect of job satisfaction on employee performance; a positive and significant influence of organizational culture on job satisfaction; a positive and significant effect of organizational culture on job satisfaction; a positive and significant effect of transformational leadership on job satisfaction; a positive and significant effect of organizational culture on employee performance through job satisfaction; a positive and significant effect of transformational leadership on employee performance through job satisfaction. This study proposes several recommendations for strong indicators that have a high contribution to organizational culture, transformational leadership and job satisfaction in order to improve employee performance